Signal Processing for Fiber Optic Systems - Shao, Jing; Kumar, Shiva (Recent Patents on Signal Processing (Discontinued), 2015)
This paper reviews the digital signal processing (DSP) methods used in coherent fiber optic communication systems. With the advances in high speed DSP, linear impairments such as chromatic dispersion (CD) and polarization mode dispersion (PMD) can be compensated for using fixed/adaptive equalizers. It is also possible to compensate for the interplay between dispersion and nonlinearity by digital back propagation (DBP), in which the virtual fibers whose signs of dispersion, loss and nonlinear coefficients are opposite of those of the transmission fiber, are realized in the digital domain by numerically solving the nonlinear Schrdinger equation (NLSE). DSP equalization enhances the transmission performance and error-free reach of coherent fiber optic systems significantly.
Keywords: polarization mode dispersion